Managing intrinsic pro-degradatory mechanical and cellular cycles in the development of osteochondral lesions - Kim, Seok Jung; Shetty, Asode Ananthram; Ahmed, Saif; Shetty, Neha; Lee, Sang Heon (Annals of Translational Medicine, 2019)
It is an aim of medical scientists to reverse disease. Chondral lesions that classically develop and super-specialised tissues have been the focus of many efforts in regenerative medicine to restore a biomechanically efficient, responsive, and self-sustaining equilibrium at the joint surface.